2019
DOI: 10.48550/arxiv.1908.02307
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Site-substitution in GdMnO3 : effects on structural, electronic and magnetic properties

Sudipta Mahana,
Bipul Rakshit,
Pronoy Nandi
et al.

Abstract: We report on detailed structural, electronic and magnetic studies of GdMn1−xCrxO3 for Cr doping levels 0 ≤ x ≤ 1. In the solid solutions, the Jahn-Teller distortion associated with Mn 3+ ions gives rise to major changes in the bc-plane sub-lattice and also the effective orbital ordering in the ab-plane, which persist up to the compositions x ∼ 0.35. These distinct features in the lattice and orbital degrees of freedom are also correlated with bc-plane anisotropy of the local Gd environment. A gradual evolution… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Further, due to the breaking of inversion symmetry from the helicoidal/spiral spin order, ferroelectricity arises and an inverse Dzyloshinskii-Moriya interaction is the underlying mechanism for the generation of electric polarization [50]. Besides this, the exchange striction mechanism (best known in Ca 3 CoMnO 6 ) [51,52] and metal-ligand orbital hybridization mechanisms (example: Ba 2 CoGe 2 O 7 ) [53] are also responsible for magnetically-driven ferroelectricity. Apart from these proper and improper ferroelectrics, CdTiO 3 is a unique system, in which ferroelectricity is driven by a phase transition from the centrosymmetric (Pbnm) to a non-centrosymmetric structure (Pna2 1 ) via displacement of Ti and O ions, even though the overall orthorhombic symmetry is maintained [54].…”
Section: The Fundamentals Of Ferroelectricitymentioning
confidence: 99%
See 2 more Smart Citations
“…Further, due to the breaking of inversion symmetry from the helicoidal/spiral spin order, ferroelectricity arises and an inverse Dzyloshinskii-Moriya interaction is the underlying mechanism for the generation of electric polarization [50]. Besides this, the exchange striction mechanism (best known in Ca 3 CoMnO 6 ) [51,52] and metal-ligand orbital hybridization mechanisms (example: Ba 2 CoGe 2 O 7 ) [53] are also responsible for magnetically-driven ferroelectricity. Apart from these proper and improper ferroelectrics, CdTiO 3 is a unique system, in which ferroelectricity is driven by a phase transition from the centrosymmetric (Pbnm) to a non-centrosymmetric structure (Pna2 1 ) via displacement of Ti and O ions, even though the overall orthorhombic symmetry is maintained [54].…”
Section: The Fundamentals Of Ferroelectricitymentioning
confidence: 99%
“…NMR studies revealed the number of disordered states of MA + was reduced from 24 in the cubic phase to eight in the tetragonal phase and frozen (only one degree of freedom) in the orthorhombic phase [76,77]. Although there is broad agreement on the structural transitions, curiously enough, there is a huge debate on the space group of this system, with both polar and nonpolar space groups frequently reported (table 1) [34,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. It is interesting to note that all three phases have been reported to have both polar and non-polar space groups for hybrid perovskites.…”
Section: Polar and Non-polar Crystal Structuresmentioning
confidence: 99%
See 1 more Smart Citation